2016
DOI: 10.21608/ejnf.2016.74983
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses and Lactational Performance of Farafra and Saidi Sheep as Affected by Supplementation of Probiotic With Natural Antioxidants

Abstract: total of 88 ewes were used in this study in two trails (44 per each trail) to investigate the effects of supplementation of probiotic abbreviated as (Effective Microorganisms with Medicinal Herbs-EMMH) on physiological responses during thermonuteral and heat stress conditions and milk yield of two local breeds (Farafra and Saidi). The studied probiotic consisted of mixed culture of two strains of fungi (Trichoderma reesei and Aspergillus oryzae) with dry live baker's yeast (Saccharomyces cervisiae) and the mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, Hayder et al (2016) showed that estrus duration did not differ in Saidi and Farafra sheep exposed to heat stress for 2 hours and ewes supplemented with selenium yeast and sodium selenate (100 gm starch powder and 0.3 mg/kg diet) groups. In addition, Saleh and Gomaa (2016) showed that estrus duration was not affected in Farafra and Saidi ewes exposed to heat stress for 2 hours and ewes supplemented with probiotic 3 Kg/ton (rich source of vitamins) as compared with control group. In conclusion, supplementation of ASX around mating and during pregnancy could improve the reproductive performance of ewes exposed to heat stress.…”
Section: Reproductive Traitsmentioning
confidence: 98%
“…However, Hayder et al (2016) showed that estrus duration did not differ in Saidi and Farafra sheep exposed to heat stress for 2 hours and ewes supplemented with selenium yeast and sodium selenate (100 gm starch powder and 0.3 mg/kg diet) groups. In addition, Saleh and Gomaa (2016) showed that estrus duration was not affected in Farafra and Saidi ewes exposed to heat stress for 2 hours and ewes supplemented with probiotic 3 Kg/ton (rich source of vitamins) as compared with control group. In conclusion, supplementation of ASX around mating and during pregnancy could improve the reproductive performance of ewes exposed to heat stress.…”
Section: Reproductive Traitsmentioning
confidence: 98%